(untitled) (Communicare: Journal for Communication Studies in Africa, 2022)
The South African Municipal Systems Act (2000) directs South Africa’s municipalities to ensurethat it uses IDP processes as a form of public participation in its affairs. This qualitative study wasconducted in Jouberton Township in the Matlosana local municipality, North West Province, toassess the extent to which participatory communication takes place in municipal IDP processes.Using participant observation, semi-structured interviews and focus group discussions, thestudy found that community members were passive participators in municipal IDP processes inwhich their involvement was limited to being informed about what would happen or had alreadyhappened. Dialogue was facilitated through a top-down modernisation-based approach, andno evidence emerged of community empowerment in decision making regarding developmentprojects. The findings suggest a need for the application of bottom-up participatory communicationand “empowered” participation during municipal IDP processes. They also suggest a need forfurther research on how “participation as an end” can be theorised in line with participatorycommunication in a complex municipal system that already requires “participation as a means”to achieve certain goals.